The lands west of the lakes; A history of the Ajattappareng kingdoms of South Sulawesi 1200 to 1600 CE - Druce, Stephen C. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2009)
The period 1200-1600 CE saw a radical transformation from simple chiefdoms to kingdoms (in archaeological terminology, complex chiefdoms) across lowland South Sulawesi, a region that lay outside the 'classical' Indicized parts of Southeast Asia. The rise of these kingdoms was stimulated and economically supported by trade in prestige goods with other parts of island Southeast Asia, yet the development of these kingdoms was determined by indigenous, rather than imported, political and cultural precepts. Starting in the thirteenth century, the region experienced a transition from swidden cultivation to wet-rice agriculture; rice was the major product that the lowland kingdoms of South Sulawesi exchanged with archipelagic traders. Stephen Druce demonstrates this progression to political complexity by combining a range of sources and methods, including oral, textual, archaeological, linguistic and geographical information and analysis as he explores the rise and development of five South Sulawesi kingdoms, known collectively as Ajattappareng (the Lands West of the Lakes). The author also presents an inquiry into oral traditions of a historical nature in South Sulawesi. He examines their functions, their processes of transmission and transformation, their uses in writing history and their relationship to written texts. He shows that any distinction between oral and written traditions of a historical nature is largely irrelevant, and that the South Sulawesi chronicles, which can be found only for a small number of kingdoms, are not characteristic (as historians have argued) but exceptional in the corpus of indigenous South Sulawesi historical sources. The book will be of primary interest to scholars of pre-European-contact Southeast Asia, including historians, archaeologists, anthropologists, linguists and geographers, and scholars with a broader interest in oral tradition and the relationship between the oral and written registers Stephen Druce obtained his PhD from the Centre for South-East Asian Studies, University of Hull. He has published on South Sulawesi history and archaeology in English and Indonesian language journals.